Effects of Job Incumbents' Race and Sex of Evaluations of Managerial Performance - Hall, Francine S.; Hall, Douglas T. (Academy of Management Journal, 1976)
The article focuses on a study which investigated the impact of a job incumbent's race and sex on managerial performance evaluations. Subjects consist of undergraduate students enrolled in an introductory management course at Michigan State University during the spring semester of 1974. They were presented with a case history and asked to complete a questionnaire. The managerial role of personnel director was selected for the study. Findings of the study suggest that race and sex of job incumbents do not affect performance appraisal.